AKUMULASI NITRAT PADA KUBIS BUNGA (Brassica Oleraceae Var Botrytis L.) DI DESA PLUMBON KECAMATAN TAWANGMANGU KABUPATEN KARANGANYAR - Rossi Prabowo; Renan Subantoro (Universitas Wahid Hasyim, 2013)
Excessive fertilization and pesticides will lead to soil and water receives more weight than chemical content,which resulted in pollution of the environment in which the growth of plants. This study aims to determine the nitrate content in the roots , stems and leaves of cabbage and nitrate in agricultural land in the village Plumbon, Tawangmangu Karanganyar. This study is a descriptive survey , which determines the content of nitrates in vegetables cabbage. This study was performed on March until September 2013. From research to know that the concentration of nitrate (NO 3-) at a depth of 0 cm -20 cm ranged between 10.98 ppm - 70.32 ppm, the accumulation of nitrate (NO 3-) at a depth of 20 cm - 40 cm ranged between 20.21 ppm - 240 ppm , the accumulation of nitrate (NO 3-) at a depth of 40 cm - 60 cm ranged between 20.53 ppm - 180 ppm. Accumulation of nitrate (NO 3-) at this depth is affected by the process of leaching and leaching of nitrate in the soil layer above it. Accumulation of nitrate in cabbage leaves are below the limits Decision No. 1168 / Men / Per / 1999 on food consumption , but the roots are already exceed the quality standards set.. Keyword : Accumulation, Nitrate, Cabbage